Membangun Masa Depan: Mengajar Bahasa Inggris Kepada Anak-Anak Sekitar - Herdi Ramon; Mas Andika Fahreza; Fadhilah Irawan; Rifky Sultan Nico Sembiring; Afni Suhaida; Lutvi Noviyanti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Mastering English from an early age is an important factor in preparing children to face global challenges in the future. This research aims to explore effective English language teaching methods in local communities, especially for children aged 7-12 years from lower middle socio-economic backgrounds. A qualitative approach was used through participant observation, in-depth interviews, and documentation of learning activities for 3 weeks. The research results show that interactive methods, such as games, role playing, and the use of simple technology, can improve language skills, build self-confidence, and create an enjoyable learning experience. In addition, local community involvement and parental empowerment have proven to play an important role in supporting children's learning. These findings emphasize the need for collaboration between communities, educators, and families to create sustainable and relevant learning programs. With a needs-based and technology-based approach, English language teaching can be an effective tool for building a brighter future for children.